Approximation of digital curves with line segments and circular arcs using genetic algorithms - Sarkar, Biswajit; Singh, Lokendra K.; Sarkar, Debranjan (Pattern recognition letters, 2003)
A method for approximation of digital planar curves with line segments and circular arcs using genetic algorithms is proposed. In this method, breakpoints on the digital curve are located in such a manner that when line segments and circular arcs are appropriately fitted between all pairs of adjacent breakpoints, the approximation error is minimized.